Contested citizenship in global city: Global citizenship, national identities and local identity in post-handover Hong Kong. Issue 2 (19th September 2019) - Chan, Chi Kit; Tang, Gary
Abstract : Purpose: This paper aims to unravel how the formation of Hong Kong citizenship intertwines with controversies over global citizenship, national identities and local identity in post-handover Hong Kong. It aims to engage the case study of Hong Kong to the academic dialogue surrounding global citizenship, especially its contested compatibility with national identities and various political communities. Design/methodology/approach: The data of this paper came from the territory-wide survey data conducted by the Public Opinion Programme of the University of Hong Kong (HKUPOP). The study cleans the survey data from 2008 to 2018, performs various regression models and concludes the findings based on longitudinal analyses of the dataset. Findings: Drawing upon the survey data from 2008 to 2018, this study shows that the identities of Hong Kong people, Chinese in general, ethnic Chinese and citizen of Chinese regime demonstrate varying compatibility to the identity of Global citizen. Such discrepancies are more pronounced when the data are broken down into the youth (aged 18-29) and the adults, and a temporal comparison was exercised before and after the Umbrella Movement in 2014. The identity of Global citizen is compatible to the local identity of Hong Kong people when comparing with its congruence with national identities. On the contrary, the statist national identity (citizen of People's Republic of China) indicates the least level of compatibility with the notion of Global citizen in Hong Kong. Originality/value: This paper unravels that the identity of global citizen could be more compatible with local identities at sub-national level than the national identities in Hong Kong. While scholarly deliberation of global citizenship contemplates on the moral and political responsibility beyond national interest, the case study of Hong Kong illustrates the multi-facets of national identities, and the local identity at sub-national level could have different compatibilities with the identity of global citizen. The findings could bring research implication to the studies of global citizenship.